Sonocrystallization of zeolitic imidazolate frameworks (ZIF-7, ZIF-8, ZIF-11 and ZIF-20) - Seoane, Beatriz (2012)
Zeolitic imidazolate frameworks ZIF-7, ZIF-8, ZIF-11 and ZIF-20 have been synthesized by sonocrystallization. In general, crystals obtained at lower temperatures and shorter times are smaller and have a narrower size distribution than those achieved by conventional solvothermal synthesis. Moreover, crystallization curves have been calculated from the XRD patterns and the Gualtieri?s model has been applied to simulate the extent of crystallization as a function of time. According to the parameters calculated, for ZIF-8 the nucleation rate controls the synthesis reaction, while for ZIF-11 and ZIF-20 both growth and nucleation rates are similar.